Cognitive Strategies to develop reading comprehension in junior students at Luis Ulpiano de la Torre High School - Andrade Suárez, Lidia Lisbeth (2023)
Propose cognitive strategies to develop reading comprehension in junior students at Luis Ulpiano de la Torre high school.